Skill mismatch in labor markets - Polachek, S. W.; Tatsiramos, Konstantinos; Pouliakas, Konstantinos; Russo, Giovanni, active 2017 (Emerald Publishing Limited, 2017)
The 2008 global financial and economic crisis led to a significant increase in unemployment rates in most developed economies, yet despite the rising supply of labor, a high share of employers claim that they cannot find the right talent and skills. Concerns that economic restructuring and changing skill needs associated with new technologies and workplace organization practices will not be met by an adequately skilled workforce, has placed the issue of skill mismatch - the incongruence between skill supply and skill demand - high up in the policy agenda. This volume contains eleven original research articles which deal with the linkages between education and skills and the causes and consequences of different types of skill mismatch. Topics include the way graduate jobs can be defined, the labor market decisions and outcomes of graduates, the determinants of the overeducation wage penalty, the determinants and consequences of underskilling, the wage return of skills, the impact of skill mismatch on aggregate productivity, and the role of work-related training and job complexity on skill development.
Prelims -- To be or not to be a scientist? -- Cross-national deployment of "graduate jobs" : analysis using a new indicator based on high skills use -- Deconstructing theories of overeducation in europe : a wage decomposition approach -- The changing occupational distribution by college major -- Skilled or educated? educational reforms, human capital, and earnings -- Labor market mismatch and labor productivity : evidence from piaac data -- Much ado about nothing? the wage penalty of holding a PhD degree but not a PhD job position -- Rethinking under-skilling in Europe -- Are skill deficits always bad? toward a learning perspective on skill mismatches -- Work-related learning and skill development in Europe : does initial skill mismatch matter? -- Job design and skill development in the workplace -- Index.
Includes index.
Print version record
Keywords: Labor economics -- Research; Business & Economics -- Economics -- General; Labour economics